Effects of Transcranial Direct Current Stimulation for Treatment of Primary Dysmenorrhea: Preliminary Results of a Randomized Sham-Controlled Trial. Issue 12 (10th September 2019) - Pegado, Rodrigo; Silva, Luana Karyne; da Silva Dantas, Hégila; Andrade Câmara, Hialison; Andrade Mescouto, Karime; Silva-Filho, Edson Meneses; Lopes, Johnnatas Mikael; Micussi, Maria Thereza Albuquerque Barbosa Cabral; Correia, Grasiéla Nascimento
Abstract: Objective: The aim of this trial was to investigate the effects of five consecutive sessions of anodal transcranial direct current stimulation (tDCS) over the motor cortex (M1) on pain, mood, and physical performance in patients with primary dysmenorrhea (PDM). Design: This is a double-blind randomized controlled trial. Subjects: Twenty-two participants with PDM according to the No. 345-PDM Consensus Guideline were included. Methods: Eleven active treatment and 11 sham stimulation patients received five applications over a one-week period. The primary outcome measures were pain evaluated by numeric rating scale (NRS) and McGill Questionnaire score. Secondary outcomes measures were responses to the Positive and Negative Affect Schedule (PANAS), Hamilton Anxiety Scale (HAM-A), grip strength, and six-minute walk test (6MWT). Baseline data were performed during the first menstrual cycle, and during the second menstrual cycle, participants were conducted to tDCS treatment, and postintervention data were collected. Results: The intervention provided significant improvements on NRS in active tDCS, shown as an interaction between group intervention vs pre/postintervention vs days of menstrual cycle (Wald x 2 = 10.54, P = 0.005), main effect of days of menstrual cycle (Wald x 2 = 25.42, P < 0.001), and pre/postintervention (Wald x 2 = 6.97, P = 0.008). McGill showed an interaction effect between pre/postintervention and group of stimulation (Wald x 2 = 18.45, P = 0.001), with a large reduction in active tDCS ( P < 0.001, d = 0.75). Psychological and functional outcomes did not differ between groups or pre/postintervention. Conclusions: tDCS could provide pain relief in subjects with PDM. These results provide some preliminary evidence for the potential role of tDCS as a contributor to the management of symptoms of PDM.